2023
DOI: 10.7759/cureus.45067
|View full text |Cite
|
Sign up to set email alerts
|

Scaphoid Plate Osteosynthesis in Complex Fractures and Wrist Trauma: A Case Series

Chai Jiun Liau,
Siew Khei Liew,
Syahril Rizal Arsad
et al.

Abstract: Introduction Treatment of scaphoid fracture is challenging due to its unique blood supply and geometry. Traditionally, a headless compression screw is the standard treatment for unstable scaphoid fracture. Some fractures are complex, for example, comminution with bone loss. A scaphoid plate is an option in these difficult fractures providing adequate rotational stability. Aim To share our experience in using scaphoid plates in complex wrist trauma and comminuted fractures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…For this specific healing mode of the scaphoid, rigid internal fixation with compression to eliminate the intra-fragmental gap and mobilization would seemly be mandatory [ 3 , 4 ]. Screw plays a major role in the implant for the broken scaphoid, while there is technically demanding much difficult in plates [ 5 , 6 ]. Dodds et al demonstrated the longest possible screw placed centrally and deep in both the proximal and distal scaphoid poles would have biomechanical superiority in for the fracture fixation stabity [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…For this specific healing mode of the scaphoid, rigid internal fixation with compression to eliminate the intra-fragmental gap and mobilization would seemly be mandatory [ 3 , 4 ]. Screw plays a major role in the implant for the broken scaphoid, while there is technically demanding much difficult in plates [ 5 , 6 ]. Dodds et al demonstrated the longest possible screw placed centrally and deep in both the proximal and distal scaphoid poles would have biomechanical superiority in for the fracture fixation stabity [ 7 ].…”
Section: Introductionmentioning
confidence: 99%